2014
DOI: 10.1155/2014/472129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing (Boiling and Roasting) on the Nutritional and Antinutritional Properties of Bambara Groundnuts (Vigna subterranea [L.] Verdc.) from Southern Kaduna, Nigeria

Abstract: This research analyzed the effect of processing (boiling and roasting) on the proximate, antinutrient, and mineral composition of Vigna subterranea seeds. The proximate composition analysis showed significant difference (P<0.05) between the levels of crude lipid, crude fiber, gross energy, carbohydrate, and moisture content in the raw and processed V. subterranea. However, no significant difference (P<0.05) was observed in protein content of processed V. subterranea as compared to the raw seeds. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
62
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 15 publications
16
62
1
2
Order By: Relevance
“…But in case of soaking in cow urine and germination fat may be utilized for metabolic activity in seeds. The results in the present study were on par with the observations stated by D'souza, (2013) for processed field bean; Uche Samuel Ndidi et al, (2014a) in Bambara groundnut,, Uche Samuel Ndidi et al, 2014b) in Sphenostylic steno carpa seeds, Audu and Aremu (2011) and Saulawa et al,(2014) et al (2016) in lima bean seeds. Crude fibre decreased by boiling and roasting in Bambara groundnut (Ndidi et al, 2014a) and kidney beans seed flour (Olanipekun O.T.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…But in case of soaking in cow urine and germination fat may be utilized for metabolic activity in seeds. The results in the present study were on par with the observations stated by D'souza, (2013) for processed field bean; Uche Samuel Ndidi et al, (2014a) in Bambara groundnut,, Uche Samuel Ndidi et al, 2014b) in Sphenostylic steno carpa seeds, Audu and Aremu (2011) and Saulawa et al,(2014) et al (2016) in lima bean seeds. Crude fibre decreased by boiling and roasting in Bambara groundnut (Ndidi et al, 2014a) and kidney beans seed flour (Olanipekun O.T.…”
Section: Resultssupporting
confidence: 89%
“…The minor decrease in protein content in cooking, autoclaving and soaking beans for short duration might be due to leaching of soluble proteins with cooked water, but the protein content increases during soaking for 24 hours and germination for 48 hours due to increase water activity as a result of induction of hydrolytic enzymes which enhances metabolic activity for protein synthesis in seeds (Bau et al, 1997). Uche Samuel Ndidi et al (2014a) reported non-significant (P<0.05) change in roasted Bambara groundnut protein content compared to raw sample. The ether extract of RBS, GBS, RoBS and CUTBS was 17.79, 14.26, 16.99 and 15.49 percent respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, partial or total replacement of protein in fish meal with plant sources has been an area of focus in aquaculture nutrition research. Lima bean (Phaseolus lunatus) has been previously studied as an alternative protein source in fish diet and seems to be a promising protein source (Adeparusi and Ajayi, 2004;Falaye et al, 2014;Ndidi et al, 2014). The results of the present study indicated that water quality parameters (temperature, dissolved oxygen, pH, nitrites and nitrates) throughout the experimental period were within the optimal range of common carp production (Zaykov and Staykov, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…The study was carried out between August and October 2015, in a private fish farm at Batié (LN: 5°17'0''-5°18'53'' and LE: 10°17'0''-10°19'31'') in the West Region of Cameroon (Njouokou et al, 2013;Zango et al, 2016). A total of 450 Cyprinus carpio fry weighing 0.97±0.03 g were obtained from the semi-artificial breeding in the same private fish farm and acclimatized in 6000 L rectangular cement tank for 3 days prior to the experiment.…”
Section: Experimental Fishmentioning
confidence: 99%
See 1 more Smart Citation